2018
DOI: 10.1111/padr.12127
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Decision‐Making and Intimate Partner Violence in Peru

Abstract: Using the continuous Demographic and Health Surveys (2005-2012) for Peru, we employ multinomial logistic regression estimates to assess risk for intimate partner violence (IPV). Using empowerment and gender frameworks for IPV, we find that women making more household decisions jointly are less likely to experience physical violence. We also find that education is negatively associated with IPV, unless a woman's attainment exceeds her partner's. Although women earning more than their partners are more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 62 publications
9
22
0
Order By: Relevance
“…Women who made decisions jointly with their husband/partner, however, had the lowest risk of psychological, physical, or sexual violence. Our results are in agreement with numerous reports from a diverse population of women (Jewkes, 2002;Hindin & Adair, 2002;Gage, 2004;Rahman, Nakamura, Seino, & Kizuki, 2013;Svec & Andic, 2018;Xu, Kerley, & Sirisunyaluck, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Women who made decisions jointly with their husband/partner, however, had the lowest risk of psychological, physical, or sexual violence. Our results are in agreement with numerous reports from a diverse population of women (Jewkes, 2002;Hindin & Adair, 2002;Gage, 2004;Rahman, Nakamura, Seino, & Kizuki, 2013;Svec & Andic, 2018;Xu, Kerley, & Sirisunyaluck, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…The chances of physical, emotional and sexual violence were decreased among women who had decision making autonomy than their counterparts. This nding is in line with other studies that was conducted in Uganda (37), in Ghana (33) and in Peru (32). This consistency could be supported by a male-dominated marital power structure has been documented to be highly related with marital con ict and husband-to-wife violence (48).…”
Section: Discussionsupporting
confidence: 91%
“…Researchers using the continuous Peru DHS from 2005-2012 found that each additional joint decision was associated with 9 percent lower odds of moderate physical violence and 16 percent lower odds of severe physical violence. They also found that women-only decision making did not have a signi cant effect on IPV (15). We found that joint-decision making was more strongly protective against IPV than women-alone decision making.…”
Section: Resultssupporting
confidence: 46%
“…(12,13). Some studies report that women-alone decision making is not signi cantly associated with IPV, while joint-decision making is a protective factor (14,15). Other studies have found that joint-decision making is negatively associated with IPV, while women-alone decision making is positively associated with IPV (16).…”
Section: Introductionmentioning
confidence: 99%